PENGEMBANGAN MEDIA AUDIO VISUAL BERBANTU APLIKASI ARTICULATE STORYLINE 3 UNTUK MENINGKATKAN MINAT BELAJAR SISWA MATERI METAMORFOSIS KELAS IV SDN - Desi Oktaria; Sujarwo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop audio visual media assisted by the articulate storyline 3 application to increase students' interest in learning metamorphosis material for class IV SDN. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages, namely 1) analysis (analysis), planning (design), development (development), implementation (implementation), evaluation (evaluation). The instruments used to collect data are observation, questionnaires and documentation given to several expert reviewers, namely media expert reviewers, material reviewers, teacher response reviewers, student responses and student learning interests. The results of this research show that audio visual media is assisted by the articulate storyline 3 application to increase students' interest in learning about metamorphosis material for class IV SDN "Very Eligible" with details of the percentage of feasibility, effectiveness, validity and increasing student interest in learning given by media review experts at a percentage of 87% , material review experts at a percentage of 88%, teacher response review experts at a percentage of 90%, student response experts at a percentage of 92% and student interest in learning at 87%. From these scores it can be said that audio visual media is assisted by the Articulate Storyline 3 application to increase students' interest in learning metamorphosis material for class IV SDN "Very Worthy" for use during the learning process.